Reality Counseling Approach to Reducing Students Learned Helplessness (Experimental Study on Class IX Students at SMPN 2 Sobang 2023/2024 Academic Year) - Sumarni, Nunung; Widiatmoko, Mualwi (International Journal of Applied Guidance and Counseling, 2024)
This research aims to determine the effectiveness of reality counseling services using a group counseling setting to reduce students learned helplessness. This research uses a quantitative method, a quasi-experimental design type. The sample and population of the study were class IX students of SMPN 2 Sobang who were divided into experimental groups and control groups. The data collection technique used was a learned helplessness questionnaire prepared by researchers, while hypothesis analysis used the Wilcoxon test using SPSS 25 software for Windows. The results of the study showed that after being given treatment there was a difference in the average pre-test and post-test scores. Hypothesis testing using the Wilcoxon test results obtained by Asymp. Sig (2-tailed) is 0.029 < 0.05. The interpretation that can be concluded is that there is a difference in the learned helplessness scores of the control and experimental classes. Thus, it can be interpreted that reality counseling is effective in reducing students' learned helplessness.